Between Secularity and Ultra-Orthodoxy: The Cultural Conflict between Hilonim and Haredim and Its Impact on Israel’s Cultural Security - Kosiorek, Piotr; Szydzisz, Marcin; Szyszlak, Elżbieta (Historia i Polityka, 2024)
This study deals with the dispute between secular Jews (Hilonim) and Orthodox Jews (Haredim) that is taking place in Israel today. Because of its nature – it concerns values, lifestyles, religion, worldview, and identity issues – it can be categorised as a cultural conflict. They represent one of the most significant challenges to cultural security. The case of Israel is no different. This paper looks closely at the determinants of the dispute between Haredim and Hilonim and the critical issues at stake. The discussion is placed in the context of Israel’s major cultural security issues.